The Safety and Biological Activity of OTT166, a Novel Topical Selective Integrin Inhibitor for the Treatment of Diabetic Eye Disease A Phase 1b Study - Boyer, David S (Ophthalmic surgery, lasers & imaging retina, 2022)
BACKGROUND AND OBJECTIVES: To evaluate the safety, tolerability, and biological activity of a topical selective integrin inhibitor (OTT166) eyedrop administered BID for diabetic retinopathy (DR) and diabetic macular edema (DME)